Nitrogen recovery in reclaimed mine soil under different amendment practices in tandem with legume and non‐legume revegetation: A review. (22nd February 2022) - Kumari, Sneha; Maiti, Subodh Kumar
Abstract: Nitrogen (N) supply is the major limiting nutrient in most reclamation schemes. In reclaimed mine soil (RMS), examining the N dynamics can be especially informative for understanding constraints on recovery that restrict revegetation success. Scholarly studies worldwide have focused on exogenous N incorporation to alleviate N shortages in the agriculture, and forestry sectors. Currently, growing concerns for the negative consequences of mining have highlighted N deficiency as one of the most significantly identified abiotic limits. Only a few researchers have focused on the N transformation mechanisms in drastically altered mine soils. The review comprises the last 10 years' research on mine reclamation approaches using legume and non‐legume plant communities. Also the capacity of different amendments to alleviate N shortages in mine soils is emphasized. The major findings of the present review suggest: (i) Revegetation using legume and non‐legume species is a self‐sustaining and economical alternative to mineral N fertilizer application; however, they cannot fully activate the biological N cycle in RMS. (ii) A more biological amendment‐assisted revegetation would enhance the key concepts of "soil‐biomass N balance" and would be ideal for N recovery in imbalanced mine soil. Altogether, grass‐legume seeding offers a potentially valuable mine reclamation tool for managing N and addressing the challenges of sustainable development.